Mechanisms involved in the development of chemotherapy-induced neuropathy. (July 2015) - Boyette-Davis, Jessica A; Walters, Edgar T; Dougherty, Patrick M
SUMMARY : Chemotherapy-induced peripheral neuropathy (CIPN) is a debilitating and painful condition seen in patients undergoing treatment with common agents such as vincristine, paclitaxel, oxaliplatin and bortezomib. The mechanisms of this condition are diverse, and include an array of molecular and cellular contributions. Current research implicates genetic predispositions to this condition, which then may influence cellular responses to chemotherapy. Processes found to be influenced during CIPN include increased expression of inflammatory mediators, primarily cytokines, which can create cascading effects in neurons and glia. Changes in ion channels and neurotransmission, as well as changes in intracellular signaling and structures have been implicated in CIPN. This review explores these issues and suggests considerations for future research.